2019
DOI: 10.1002/adfm.201808092
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Dioxide in Carbon Nanoreactors as a Catalytic Nanosponge for the Efficient Desulfurization of Liquid Fuels

Abstract: The principle of a "catalytic nanosponge" that combines the catalysis of organosulfur oxidation and sequestration of the products from reaction mixtures is demonstrated. Group VI metal oxide nanoparticles (CrO x , MoO x , WO x ) are embedded within hollow graphitized carbon nanofibers (GNFs), which act as nanoscale reaction vessels for oxidation reactions used in the decontamination of fuel. When immersed in a model liquid alkane fuel contaminated with organosulfur compounds (benzothiophene, dibenzothiophene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…POMs, in particular Keggin‐type POMs, have been reported to show remarkable ODS activity after incorporating with MOFs. [ 33–35 ] The Keggin‐type phosphomolybdate acid (PMA, H 3 PMo 12 O 40 , P/Mo = 1/12) itself shows certain ODS activity. PMA possesses four kinds of oxygen atoms (Figure 1b): the tetrahedral oxygen (O a ) coordinated with heteroatom P, the bridging oxygen (O b ) connected with different trimetallic clusters (Mo 3 O 10 ), the bridging oxygen (O c ) in the same trimetallic cluster (Mo 3 O 10 ), and the terminal oxygen (O d ).…”
Section: Introductionmentioning
confidence: 99%
“…POMs, in particular Keggin‐type POMs, have been reported to show remarkable ODS activity after incorporating with MOFs. [ 33–35 ] The Keggin‐type phosphomolybdate acid (PMA, H 3 PMo 12 O 40 , P/Mo = 1/12) itself shows certain ODS activity. PMA possesses four kinds of oxygen atoms (Figure 1b): the tetrahedral oxygen (O a ) coordinated with heteroatom P, the bridging oxygen (O b ) connected with different trimetallic clusters (Mo 3 O 10 ), the bridging oxygen (O c ) in the same trimetallic cluster (Mo 3 O 10 ), and the terminal oxygen (O d ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the calculated energy barrier for Cl − exchange in the S N 2 reaction within nanotubes was higher by 6.6 kcal/mol in comparison with the gas phase [69]. Later, it was shown that SWCNTs may be used as effective nanoreactors for preparative syntheses of inorganic [70] and organic [71][72][73][74][75] products with high yields; it is also possible to achieve enantiomeric excess of the products by using a racemic mixture of P and M enantiomers of (n,m) chiral nanotubes [76].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the advantages of ODS, various types of catalyst such as polyoxometalates, ionic liquids and metal oxides have been developed. Tungsten trioxide (WO 3 ) has been applied in various fields because of its acidic and thermal stability and good crystallinity .…”
Section: Introductionmentioning
confidence: 99%
“…During the process of ODS, organic sulfur compounds can be oxidized under mild conditions to sulfones or sulfoxides, which can be easily removed by polar extractants. 7,8 Based on the advantages of ODS, various types of catalyst such as polyoxometalates, 9,10 ionic liquids 11 and metal oxides 12,13 have been developed. Tungsten trioxide (WO 3 ) has been applied in various fields because of its acidic and thermal stability and good crystallinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation